Morphological characteristic of Ludai (sapium baccatum) / Nur Farahin Salleh - Salleh, Nur Farahin (Faculty of Applied Sciences, 2016)
The scientific name of Ludai is Sapium baccatum. This species has the potential to be used for wood composite product in the furniture industry and wood plastic composite product. However, information about these Sapium baccatum is still inadequate especially those related to the morphological characteristic. In this study, morphological characteristic are carried out because of its importance to determine its fiber length, fiber diameter, lumen diameter and cell wall thickness towards different height portion and distance (from near bark to near pith). Runkel ratio and felting power are also calculated to determine the suitability of fiber in terms of producing a quality paper. The highest average recorded for fiber length, fiber diameter, lumen diameter and cell thicknesses are 1.217mm, 44.88IJm, 31.331Jm and 13.561Jm respectively. While the highest runkel ratio and felting power recorded for Sapium baccatum are more than 1 and less than 60 percent. The result shows that this species is suitable for paper making.